1977
DOI: 10.1111/j.1365-3032.1977.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of chemoreceptor function in army worm larvae (Spodoptera exempta) by a plant‐derived sesquiterpenoid and by sulfhydryl reagents

Abstract: ABSTRACT. Warburganal, a sesquiterpene dialdehyde from Warburgia sp., strongly suppressed the feeding response of Spodoptera exempta larvae to sucrose‐flavoured agar. Its effect on chemoreceptive sensilla of S. exempta was investigated. After a latent period (of up to an hour, depending on concentration), sensilla treated with warburganal produced transient bursting discharges in several receptor cells. Subsequently, receptor responses to sucrose or meso‐inositol were reversibly inhibited. These effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We have previously demonstrated that the relative antifeedant activities of 1 , 2 , and 3 were correlated with their relative agonism of mosquito TRPA1 channels and that TRPA1 was essential for the antifeedant activity of 1 [20]. The strong antifeedant activity of 9 and 10 is likely due to agonism of TRPA1 channels because both are potent agonists of vertebrate TRPA1 channels [62,63] and known antifeedants against a wide variety of insects [64,65,66,67,68]. The electrophilic aldehyde groups of 1 , 9 , and 10 are likely critical for interacting with nucleophilic cysteine and lysine residues in the NH 2 -terminal domain of TRPA1 channels [20,69,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the relative antifeedant activities of 1 , 2 , and 3 were correlated with their relative agonism of mosquito TRPA1 channels and that TRPA1 was essential for the antifeedant activity of 1 [20]. The strong antifeedant activity of 9 and 10 is likely due to agonism of TRPA1 channels because both are potent agonists of vertebrate TRPA1 channels [62,63] and known antifeedants against a wide variety of insects [64,65,66,67,68]. The electrophilic aldehyde groups of 1 , 9 , and 10 are likely critical for interacting with nucleophilic cysteine and lysine residues in the NH 2 -terminal domain of TRPA1 channels [20,69,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally compounds 1, 2 and 3 are pungent to humans [47][48][49], possess antifeedant and insecticidal activity [50,51], and agonize Transient Receptor Potential A1 (TRPA1) channels [21,41,49,52,53]. Most biological activities, including the antifeedant activity, of these drimane sesquiterpenes have been attributed to the α,ß-unsaturated 1,4-dialdehyde functionality of the molecules, forming adducts with free sulfhydryl groups PLOS NEGLECTED TROPICAL DISEASES [54,55] or primary amines such as the ε-amino group of lysine [56] , [57]. Our previous results showed that 1 could effectively kill mosquito larvae in an aqueous environment, penetrate the cuticle of adult female mosquitoes, reduce the feeding of mosquitoes when added to a sucrose solution, and reduce the propensity of mosquitoes to blood feed when dried onto the surface of a membrane feeder.…”
Section: Derivatization Of Cinnamodialmentioning
confidence: 99%